(3GdMeGjI GdLfGFjI ddeQCI (B: s (3OQGSI ebGQfI (B/ s - (3ejGOI eLjO YHOGddg eYGQLs; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3deG cGfJ GdeQCI h HMb fUa GdeLJeY(B: (3aEf JOYje MejGJgG GdLfGFjI hGLH bGfhfi(B: (3h LOjQ HGdPcQ Cf GdJTQjYGJ GdYQHjI JaGhJJ ef MjK OQLI GdMeGjI GdeefhMI ddeQCI(B: (3EP Cf dcd eTQY SjGSJg GdOGNdjI ai QSe GdMeGjI GdebQQI(B. (3Zfi Yf GdHjGf Cf GdMeGjI JfbSe Edi MeGjI ehVhYjI JJYdb HTb GdJcdja h GdYbGH(B: (3h ef NdGdgG jJe JLQje cGaI CTcGd GdYfa h GdJejjR VO GdeQCI(B: (3cPdc JbQjQ XQha eTOOI EPG cGf GdaYd GdeLQe eMdI CfKi(B. (3CeG GdTb GdKGfi h gh GdMeGjI GdLfGFjI GdELQGFjI ddeQCI(B: (3h GdPi jJe ef NdGdg hVY NUhUjI ai GdELQGAGJ dgG(B: (3ShGA cGfJ ai eQMdI GdJMbjb Gh eQMdI GdeMGceI(B: (3ceG dh MXQ GdbGfhf JaJjT GdeQCI EdG ef Hfj LfSgG(B. (3Hd de JbJUQ Mbhb GdeQCI Edi gPG GdMO(B: (3h EfeG JYOGg Edi eG HYO GdeMGceI(B: (3aChLH ai MGdGJ eYjfI JCLjd JfajP GdYbhHI(B: (3ceG Chdi ddeQCI GdSLjfI Mbhb gGeI CKfGA aJQI EfRGdgG ai GdSLhf(B. (3jJHOi ddaGMU eOi CgejI UaI CKQ GdCfhKI Ydi GdbGfhf GdLfGFi GdehVhYi h GdELQGFi(B: (3h eOi JeJYgG HJdc GdMbhb GdgGeI GdJi bQQJgG cdG ef OSGJjQ GdOhd(B: (3aVdG Yf GdGJaGbjGJ h GdehGKjb GdOhdjI GdJj YfjJ HGdfU Ydi Mbhb GdeQCI hMeGjJgG h YOe GdJejjR h GdYfa VOgG(B: (3CjG cGf fhYg Ch OQLJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B353-367s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI GdELgGV s; (3LQjeI NWa GdeQCIs; (3LQjeI GdHdWLI VO GdeQCIs; (3LQjeI NJGf GdEfGK s; (3LQjeI GdJMQT GdLfSjs; (3eGgjI GdMeGjI GdLfGFjI ddeQCIs; (3LQjeI GdRfGs; (3LQjeI gJc GdYQVs; (3MeGjI GdeQCI ef GdHZGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs